Stelis breviloba (Orchidaceae, Pleurothallidinae), a new species from Mexico - Rodolfo Solano; Gerardo A. Salazar (Botan‪ical Sciences, 2023)
Background: Stelis subgen. Physosiphon is basically a Meso-American group, and its best-known species is Stelis emarginata, characterized by its reddish orange flowers and distribution along the Gulf of Mexico slope in Mexico and Guatemala. Morphologically similar specimens from the Sierra Madre del Sur, on the Pacific slope of Guerrero and Oaxaca could represent a different and undescribed taxon.